L'architecture ibadite : éloge de la simplicité, retour aux sources de l'islam - Prevost, Virginie (Monumentum: l'Habitation, le Politique, le Sacré, 2016)
Keywords: Architecture – Sources

A document of ibadi fiqh governing the architecture of mosques - Benkari, Naïma (Journal of Islamic Architecture, 2016)
In spite of a long-standing interest in the Ibadi community and its historical, social, religious and architectural legacy, its Ibadi scholarly literature remains largely unknown. The present research continues in the footsteps of the pioneering works of Joseph Schacht (Schacht, 1954) and Pierre Cuperly (Cuperly, 1988) on Ibadism. It aims to cast light on the Ibadi literature that represents an authentic source of information for the study of Ibadism past and present. This article analyzes an Ibadi manuscript from the twelfth century written by the scholar Abul’Abbas Ahmad. This document has been the primary reference for the most important sources of Ibadi legislation still in use by the community in its three main centers: M’zab, Djerba and Oman. The study of this document, along with other Ibadi scholarly literature on this topic, shows that this jurisprudence has regulated in detail the design, construction and management of mosques, and that this level of careful attention was due to the importance of the mosque for the instruction and organization of the community.
Keywords: Architecture – Sources; Fiqh